Equity Prices and Monetary Policy: An Overview with an Exploratory Model - Alexandre, Fernando (2001)
Financial stability, with an emphasis on the relevance of asset prices stability to the stability of the overall economy, has become the subject of wide discussion among monetary authorities. Closely related to these issues are the concerns of central bankers with a bubble economy and its aftermath. After briefly surveying the potential links between financial markets and the real economy and its implications for the design of monetary policy, we illustrate some of the issues in this literature through the analysis of a simple linear rational expectations model. From this exercise we conclude that the benefits of reacting to asset prices depend crucially on the kind of shock hitting the economy. Ideally, reacting to the misalignment of equity prices is desirable. However, the presence of uncertainty in the estimation of the variables to which the policy rule responds may overturn this conclusion.